The untapped skills of hospital pharmacists in South Africa: How can pharmacists improve service delivery in preparation for National Health Insurance? - Chuene, Tiisetso Aubrey; Moloto, Noko (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2023)
Background: The tertiary education of a pharmacist in South Africa covers a wide range of expertise; however, many of these skills remain untapped more especially at the public health facilities. To meet the National Health Insurance's goals, the role of a pharmacist is anticipated to change as they will be required to embark on a more integrative role by shifting from product-centered focus to a patient-centered approach. Aim: The aim of this review is to explore the untapped skills of public hospital pharmacists as a way of improving service delivery in preparation for National Health Insurance. Methods: A secondary qualitative technique using desktop approach served as the foundation for this research. The study used thematic content analysis to identify and analyse the roles of hospital pharmacists. Results: The findings of this article indicate that pharmacists can play different roles within the public hospital setting to improve service delivery. The identified roles are: provision of Pharmacists Initiated Therapy, the integration of pharmacists into the wards, the involvement of pharmacists as part of the multidisciplinary healthcare team and the utilisation of specialities such as clinical pharmacists' services. Conclusion: To improve service delivery and promote the idea of holistic pharmaceutical care, it is crucial that the hospital pharmacist delegate responsibilities and functions related to product supply to pharmacist's assistants as this will give pharmacists more time for patient-focused roles.